Educação matemática e as implicações sociais da tecnociência na engenharia - Gaffuri, Stefane Layana (2021)
The present thesis aims to emphasize the importance and seek a way to discuss the social implications of technoscience in engineering courses in mathematics. This need is due to the new techno-social relations, accelerated by the fourth industrial revolution. For this, a possibility is presented to subsidize the reflections of engineering students to think about their interventions in the world, that is, through the creation or use of social technologies. It is understood that mathematics is a socially constructed science and is present in several branches of social activities, producing subsidies for technological and human development. It contributes to the underlying formation of scientific and technological constructs, so there is an urgent need to rethink the relationship between mathematics, engineering, and society. Therefore, it is argued that mathematics education needs to go beyond the prototypes of technical rationality since there is a deep-rooted conception of knowledge transmission. To this end, the guiding question of the reflections of this research is, "What is the relationship between mathematics education and the social implications of technoscience in the education of engineers?" The bibliographical research was based on a new look on technological education in the face of contemporary civilizational challenges, basing itself on Bazzo, from the concept of Science, Technology, and Society (CTS) by agreeing with the idea of a more "disobedient" education and by accepting Skovsmose's invitation to seek a Critical Mathematics Education, and in this way rethinking the technological development model discussed through mathematics by Civiero (2016) and extended to Engineering by Bordin (2018). As a resource to identify new curricular and performance possibilities for mathematics education in engineering, it was investigated, through a case study, how mathematics teachers, from engineering courses at the Federal Technological University of Paraná (UTFPR) understand the relevance of mathematical knowledge and its implications facing the involvement of this discipline with techno-scientific issues. With the intention of gathering information to answer the research problem through direct contact with the situation object of study, the methodological proposal of this thesis was built based on a qualitative research approach, developed from two movements, the bibliographic and the empirical research. In the empirical research, the production of data occurred through semi-structured interviews with mathematics teachers who teach in the engineering courses of the institution. The resulting categorizations and analyses were done by means of the Textual Discourse Analysis (TDA) methodology. The problematizations, discussions, and propositions resulting from the bibliographic and empirical work are circumscribed to the following categories of analysis, (a) the teaching practice and the scientific and technological understandings of mathematics teachers in engineering, (b) the relations between the social dimensions and mathematical knowledge in engineering courses, (c) the teaching activities and their articulations with contemporary variables, and (d) the mathematics teacher in engineering and the need for continuous updating. Despite important initiatives, the conceptions and teaching activities reveal a long way to go in overcoming historically consolidated rational formative models to deepen epistemological and human issues beyond technical rationality.